2013
DOI: 10.1017/jfm.2013.469
|View full text |Cite
|
Sign up to set email alerts
|

Flow past a rotationally oscillating cylinder

Abstract: Flow past a circular cylinder executing sinusoidal rotary oscillations about its own axis is studied experimentally. The experiments are carried out at a Reynolds number of 185, oscillation amplitudes varying from π/8 to π, and at non-dimensional forcing frequencies (ratio of the cylinder oscillation frequency to the vortex-shedding frequency from a stationary cylinder) varying from 0 to 5. The diagnostic is performed by extensive flow visualization using the hydrogen bubble technique, hotwire anemometry and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 51 publications
10
47
0
Order By: Relevance
“…The mean wake profile and wake modes were found to be similar at spanwise locations located at mid-span and ∼0.75D above and below mid-span, as would be expected if the rotary forcing aligned the shedding with the cylinder. Based on these results, and the results of Poncet (2002), Jian et al (2007) and Kumar et al (2013), it is reasonable to speculate that the shedding is parallel and nominally two-dimensional everywhere along the span of the cylinder, except very close to the boundaries due to end effects. This does not exclude the possible existence of small-scale three-dimensional structures that have not been captured due to experimental limitations.…”
Section: Experimental Set-upmentioning
confidence: 53%
See 3 more Smart Citations
“…The mean wake profile and wake modes were found to be similar at spanwise locations located at mid-span and ∼0.75D above and below mid-span, as would be expected if the rotary forcing aligned the shedding with the cylinder. Based on these results, and the results of Poncet (2002), Jian et al (2007) and Kumar et al (2013), it is reasonable to speculate that the shedding is parallel and nominally two-dimensional everywhere along the span of the cylinder, except very close to the boundaries due to end effects. This does not exclude the possible existence of small-scale three-dimensional structures that have not been captured due to experimental limitations.…”
Section: Experimental Set-upmentioning
confidence: 53%
“…Experimental studies have been performed by Tokumaru & Dimotakis (1991), Fujisawa, Kawaji & Ikemoto (2001), Fujisawa, Tanahashi & Srinivas (2005), Lee & Lee (2006), Saad, Lee & Lee (2007), Lee & Lee (2008), Nazarinia et al (2012) and, most recently, Kumar et al (2013) 552 P. Sellappan and T. Pottebaum and Sellappan & Pottebaum (2014). Tokumaru & Dimotakis (1991) conducted an experimental study at Re = 15 000, performing flow visualization and wake profile measurements on circular cylinders undergoing forced rotary oscillations in a steady uniform flow and found that the drag forces on the cylinder were reduced at high oscillation frequencies while undergoing rotary forcing.…”
Section: Vortex Shedding From Cylindersmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has also been done with cylinders oscillating rotationally (Tokumaru & Dimotakis 1991;Thiria, Goujon-Durand & Wesfreid 2006;Du & Dalton 2013;Kumar et al 2013) as well as transversely (Ongoren & Rockwell 1988;Williamson & Roshko 1988;Gu, Chyu & Rockwell 1994;Blackburn & Henderson 1999;Guilmineau & Queutey 2002;Lam, Liu & Hu 2010b;Leontini, Jacono & Thompson 2011) in a cross-flow at varying amplitudes and frequencies below, equal to and above the natural shedding frequency of a stationary cylinder. Others have investigated the effects of prescribed sinusoidal translation in quiescent fluids (Williamson 1985;Justesen 1991;Dütsch et al 1998;Iliadis & Anagnostopoulos 1998;Lam, Hu & Liu 2010a).…”
Section: Introduction and Related Workmentioning
confidence: 99%